Psychological distance and pro-environmental behavior: Insights from wildfire-affected PCT hikers - Miller, Lindsay B.; Rice, Ronald E. (Frontiers in Psychology, 2025)
IntroductionAs wildfires and extreme weather events increase in frequency and severity, understanding individuals’ psychological and behavioral responses to these rising climate change impacts is necessary to cultivate pro-environmental behavior (PEB). Based on a theoretical model grounded in construal level theory and the theory of reasoned action, we propose that exposure to wildfires is associated with psychological distance of climate change, climate change and wildfire attitudes, and PEB; that psychological distance is associated with climate change attitudes and PEB; and that subjective norms are associated with PEB.MethodWe assess these associations through an a priori content analysis of 66 semi-structured interviews with Pacific Crest Trail hikers during the 2022 wildfire season, illustrated through quotes responding to interview questions asking about such associations.Results and discussionThe analyses and quotes provide initial support for the proposed model, nuanced insights into the subdimensions of each construct, and a basis for possible wildfire and climate change messaging.